Hostel management system (HMS) - Wan Nur Hidayu, Wan Ja’afar (2012)
Hostel Management is an application developed to manage the various activities in hostel.The particular project is deal with the problems on managing the a hostel and avoids the problem occurs when carried out manually.Identification of the drawbacks of the existing system leads to the designing of computerized system that will be compatible to the existing system with the system which is more friendly and more GUI oriented.The objective of this project is to present a design of Hostel Management System for SMA Pahang. Our research is a comparative study of software design in development HMS for SMA Pahang.The study is focusly on fully utilize the OO Diagram and functional-based diagram.Our focus is comparing the utilization and significant of software design while developing the system using PHP for development of HMS.